Volleyball Players Pre-Competitive Anxiety: Sex-Based Differences and Relationship with Sport Characteristics - Sintija Šadrincevaitė; Aušra Griciūtė (Baltic Journal of Sport and Health Sciences)
Background. The issue of pre-competition anxiety is multidimensional and there is still a lack of complex studies in multiple sports as well as in volleyball analysing the relationships of pre-competitive anxiety with multiple correlates.